2017
DOI: 10.1016/j.neuroscience.2016.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in serotonin signaling: Implications for early brain function, behavior and adaptation

Abstract: The neurotransmitter serotonin (5-HT) plays a central role in brain development, regulation of mood, stress reactivity and risk of psychiatric disorders, and thus alterations in 5-HT signaling early in life have critical implications for behavior and mental health across the life span. Drawing on preclinical and emerging human evidence this narrative review paper will examine three key aspects when considering the consequences of early life changes in 5-HT: (1) developmental origins of variations of 5-HT signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
171
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(182 citation statements)
references
References 216 publications
(312 reference statements)
3
171
0
8
Order By: Relevance
“…It has been suggested that pregnancy conditions such as maternal stress and inflammation up-regulate placental serotonin production to program the developing fetus for neurodevelopmental disorders (St Pierre et al 2015; Goeden et al 2016; Brummelte et al 2016). Increased IL-1 and IL-6 have been identified as potential cytokines linked to changes in placental function and subsequent neurodevelopmental insults that include forebrain damage and behavioral consequences in rodents (Smith et al 2007; Girard et al 2010).…”
Section: Long-term Outcomes Of Children Born To Obese Mothersmentioning
confidence: 99%
“…It has been suggested that pregnancy conditions such as maternal stress and inflammation up-regulate placental serotonin production to program the developing fetus for neurodevelopmental disorders (St Pierre et al 2015; Goeden et al 2016; Brummelte et al 2016). Increased IL-1 and IL-6 have been identified as potential cytokines linked to changes in placental function and subsequent neurodevelopmental insults that include forebrain damage and behavioral consequences in rodents (Smith et al 2007; Girard et al 2010).…”
Section: Long-term Outcomes Of Children Born To Obese Mothersmentioning
confidence: 99%
“…Not surprisingly, like in non-mammalian species, serotonin modulates neuronal proliferation, migration and differentiation. In addition, 5-HT is implicated in the emergence of many neuropsychiatric disorders, including mental retardation, autism, depression and anxiety [10,15,[21][22][23][24][25][26]. Importantly, 5-HT signalling is influenced by numerous epigenetic and genetic factors, including nutrition and gut microbiota [27,28], perinatal stress [29][30][31], infection and inflammation [32][33][34][35], 5-HT metabolism and storage [15,[36][37][38], pharmacological compounds such as selective serotonin reuptake inhibitors [38][39][40] and genetic alterations [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibition (5HT), caused by the use of fluoxetine, increases the extracellular concentration of this neurotransmitter, which plays important roles in the regulation of behavior, mood, anxiety, aggressiveness, depression, sleep, fatigue and appetite suppression 6 .…”
Section: Introductionmentioning
confidence: 99%